Mercury cycling in grasslands: deposition, plant uptake, and biomass-burning emissions - Irei, Satoshi (Frontiers in Environmental Chemistry, 2025)
In order to evaluate the effectiveness of the Minamata Convention on mercury, understanding the air–surface mercury exchange in grasslands is important as they cover 20%–40% of the Earth's land surface. An in-depth quantitative understanding of the processes of the mercury cycle, such as dry and wet depositions, evasion from soil, plant uptake, and natural and prescribed biomass burning, is essential to explore the mercury cycle in these regions; however, only a limited number of studies are available on these processes, and many questions regarding them still remain. In this mini-review, the key emission and sinking processes occurring in natural and semi-natural grasslands and the potential of stable mercury isotope measurements for tracing studies of mercury origin(s) in grasslands are discussed.